Dasar Pertimbangan Hakim dalam Putusan Nomor 150/PID.SUS/2021 Terhadap Pengedar Sediaan Farmasi Tanpa Ijin dalam Perspektif Keadilan: Studi Kasus Putusan Pengadilan Negeri Kupang - Diana Ndun; Orpa Ganefo Manuain; Rosalind Angel Fanggi (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
This research is a normative research, so this data is carried out by conducting a literature study on the verdict. Data sources are obtained from primary legal materials, namely: laws and regulations and court decisions, secondary obtained from literature and literature studies, tertiary legal materials obtained from the internet, dictionaries, and encyclopedias. The results of the research obtained from analyzing the verdict show that (1). The basis for the judge's consideration in imposing criminal sanctions against distributors of pharmaceutical preparations without expertise and authority by looking at the Judge's Juridical Considerations and Non-Juridical Considerations of the judge is appropriate and uses an Article that meets the elements of the perpetrator's violation in accordance with the Health Law, but the imposition of criminal sanctions is very light and far from the provisions of the Article. (2). The suitability of the imposition of criminal sanctions in Decision Number 150/Pi.Sus/2021/PN Kupang with the Health Law given by the Judge to the defendant is so light that it cannot guarantee that the defendant will feel frustrated and will not repeat his actions again. This makes the sense of justice, usefulness and legal certainty not fulfilled properly. The author's suggestion that the criminal sanctions imposed by the Panel of Judges against the defendant should not only consider the behavior and actions of the defendant but also look at the consequences of the defendant's actions that can have a bad impact on the health of consumers/patients who take the hard drug.